Twin Studies: Revealing the Genetic Basis of Malocclusion - Patel, Dolly P; Gupta, Bhaskar; Sharma, Tanmay (Journal of Orofacial Research, 2011)
The relative contribution of genes and the environment to the etiology of malocclusion has been a matter of controversy throughout the twentieth century and the first decace of twentyfirst century. Twin studies provide important insights into how genetic and environmental factors contribute to variation in dental and craniofacial morphology. This review describes research models involving twins, apart from the traditional comparison of similarities in monozygotic (identical) and dizygotic (nonidentical) pairs, throws some light on zygositydetermination, summarizes some landmark twin studies in orthodontics and future directions in dental research involving twins are outlined.